The Maiden on the Battlefield: War and Estrangement in Southey’s Joan Of Arc - Addison, Catherine (Romanticism on the Net, 2003)
AbstractCritical opinion on Southey’s Joan of Arc has tended to focus on the poem’s political function. This article acknowledges Joan’s symbolic connection with Charlotte Corday and revolutionary France, but sees the poem’s principle function as belonging to a wider context. Throughout the text, Southey’s Maid is pitted not simply against the misguided English enemy but against warfare per se. The article argues that she performs this main function by being out of place, as a young woman, on a battlefield—especially in the role of military leader. It does this by invoking Shklovsky’s theory that unfamiliarity revives human perception, whereas “habitualization” erodes it. In Joan of Arc, the Maid’s unfamiliarity, or perceived inappropriateness in context, is constantly emphasized. The reader is never allowed to forget Joan’s gender, inexperience and supernatural strangeness, for they are the cause of recurrent wonder and disgust in other characters. She is routinely named as a miracle or freak of nature and her presence hence throws everything in the largely military narrative into relief, highlighting war’s cruelties and absurdities. Joan, moreover, functions not only as a passive point of reference. She is frequently the narrator’s focalizer, her estranged viewpoint inviting the reader to substitute her spontaneous horror and compassion for epic’s usual triumphalism. The narrative is full of nauseating physical details of wounding and dismemberment, as well as exhaustive accounts of the progress of grief and starvation. In fact, as the article claims, this poem strives throughout to undo the strategies that Elaine Scarry in The Body in Pain sees everywhere working to make war’s purpose of injuring disappear. Joan, unlike more “habitualized” soldiers and leaders, never loses sight of injury in any of its forms and thus her vision forces the reader to consider all the repercussions of war, both physical and psychological.